The Psychological Impact of Military Operations on Civilians and the UN Human Rights Committee Japalali Decision: Exploring Mental Anguish under a Vida Digna, Right to Life Prism. (11th December 2020) - Solomon, Solon
Abstract: Among international scholars, much emphasis has been given on how in situations of warfare, international humanitarian law can impact upon international human rights law (IHRL). The opposite scenario has been little explored. On this account, the article will explore how under the influence of IHRL in instances of wounded civilians feeling mental anguish as a result of their uncertainty whether or not they will remain alive, a state can be found as violating these civilians' right to life vida digna facet. At the same time, the article will proceed to analyze how such vida digna mental anguish parameter must be seen not just as general carte blanche for expanding the notion of psychological injury beyond cases of mental harm in all military operations, but as relevant only in instances, like 'kill or capture' operations where the state is seen in a position to consider in advance the conditions under which a military engagement takes place.